1987
DOI: 10.1002/ijc.2910390104
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and environmental evidence of the health effects of exposure to erionite fibres: A four‐year study in the cappadocian region of turkey

Abstract: An environmental and epidemiological study has been carried out in Central Cappadocia, Turkey, aiming at investigating the relationship between exposure to naturally occurring erionite fibres and the reported high incidence of malignant mesotheliomas. Airborne fibre levels are generally low but show a higher proportion of erionite fibres in the villages affected by malignant disease than in a control village. The same pattern is confirmed by analysis of the fibre content in lung tissues of sheep from several v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
106
0
6

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(116 citation statements)
references
References 15 publications
4
106
0
6
Order By: Relevance
“…In villages built with stones mined from the nearby natural caves in Cappadocia, a region in Central Anatolia, Turkey, at least 50% of deaths are caused by malignant mesothelioma. [13][14][15][16][17] When Baris et al 13 discovered a very high incidence of mesothelioma in the village of Karain, scientists looked for asbestos, and some asbestos was found; 18 however, additional studies demonstrated that asbestos is omnipresent in Cappadocia because it is a natural component of that volcanic terrain and because asbestostremolite-based stucco has been widely used in building construction in all Cappadocian villages. 14 -17,19 Hence, asbestos could not account for the uniquely high incidence of mesotheliomas in these three villages.…”
Section: Genetic Predispositionmentioning
confidence: 99%
See 2 more Smart Citations
“…In villages built with stones mined from the nearby natural caves in Cappadocia, a region in Central Anatolia, Turkey, at least 50% of deaths are caused by malignant mesothelioma. [13][14][15][16][17] When Baris et al 13 discovered a very high incidence of mesothelioma in the village of Karain, scientists looked for asbestos, and some asbestos was found; 18 however, additional studies demonstrated that asbestos is omnipresent in Cappadocia because it is a natural component of that volcanic terrain and because asbestostremolite-based stucco has been widely used in building construction in all Cappadocian villages. 14 -17,19 Hence, asbestos could not account for the uniquely high incidence of mesotheliomas in these three villages.…”
Section: Genetic Predispositionmentioning
confidence: 99%
“…14 -17,19 Another type of mineral fiber, erionite, which had been detected in the lungs of several villagers, was suspected as causative agent. 14 -17,19 Erionite is a type of fibrous zeolite commonly found in the stones of the houses of Karain, Sarihidir, and Tuzkoy, 2,17,19,20 which, when injected intrapleurally into animals, caused mesothelioma. 21 Erionite, therefore, seemed much more potent than asbestos in causing mesothelioma because more than half of the villagers died of this disease, 17,19,22 and erionite is thought to be one of the most potent human carcinogens.…”
Section: Genetic Predispositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baris et al (1987) reported total fiber levels in the villages from 0.004-0.175 fiberslml, and these measurements included other dusts in addition to zeolite. Simonato et al (1989) reported newer estimates of fiber characteristics in Karain and Sarihidir (two of the affected villages) and found levels to be 0.002-0.010 fiberdml (-80% zeolite) and 0.001-0.029 fibers/ml (-60% zeolite), respectively.…”
Section: Erionitementioning
confidence: 99%
“…Volcanic rocks containing erionite are common in three villages -Karain, Tuzkoy and Sarihidir -which are built on and into these volcanic rocks. Although fibre levels are low, high proportions of erionite have been detected in airborne dust samples collected from these villages (2,6). Epidemiological ©2004 Pulsus Group Inc. All rights reserved ORIGINAL ARTICLE studies in these villages have shown that the incidence of MM is 1000 times higher than the reported general population incidence in Canada (7,8).…”
mentioning
confidence: 97%